Unlocking the potential of proton conductivity in guanidinium-based ionic covalent organic nanosheets (iCONs) through pore interior functionalization - Kumar, Sushil; Hu, Jiahui; Pandikassala, Ajmal; Kurungot, Sreekumar; Addicoat, Matthew A.; Szekely, Gyorgy (Applied Materials Today, 2023)
Recently, scientists have been exploring the incorporation of proton carriers such as water and phosphoric acid (PA) into the pores and channels of porous materials to enhance proton conduction performance. Ionic covalent organic nanosheets (iCONs) have been identified as promising functional materials due to their inbuilt ionic interfaces, which can facilitate strong interaction with counter ions present inside the pore structure and thus shorten ion transport pathways. However, there is a lack of research related to proton conductivity in iCONs loaded with PA. To address this, we prepared three functionalized guanidinium-based iCONs using a solvothermal condensation reaction between guanidinium amine (TG) and functionalized terephthaldehyde (Da, Dha, and Dma). PA was also incorporated into the iCON structure via ex situ loading to observe its effects on proton conduction performance. The results showed that both the iCONs and PA-iCONs were highly stable in water, organic solvents, acidic and basic media. Amongst these PA-iCONs, one with hydroxyl-functionalization (PA-DhaTG) displayed high proton conductivity at 90 degrees C and 95% relative humidity due to a Grotthuss mechanism for protons. These functionalized guanidinium-based iCONs could prove useful for applications in energy conversion devices.
Keywords: chemical stability; Functionalized pore interior; Guanidinium group; ionic covalent organic nanosheets; proton conductivity